Financial market contagion in the Asian crisis - Ilan Goldfajn; Taimur Baig (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
This paper tests for evidence of contagion between the financial markets of Thailand, Malaysia, Indonesia, Korea, and the Philippines. Cross-country correlations among currencies and sovereign spreads are found to increase significantly during the crisis period, whereas the equity market correlations offer mixed evidence. A set of dummy variables using daily news is constructed to capture the impact of own-country and cross-border news on the markets. After controlling for own-country news and other fundamentals, the paper shows evidence of cross-border contagion in the currency and equity markets.
Keywords: F30; F40; G15; 330